Neonatal Imitation, Intersubjectivity, and Children With Atypical Development: Do Observations on Autism and Down Syndrome Change Our Understanding? - Heimann, Mikael; Holmer, Emil (Frontiers in Psychology, 2021)
Almost all studies on neonatal imitation to date seem to have focused on typically developing children, and we thus lack information on the early imitative abilities of children who follow atypical developmental trajectories. From both practical and theoretical perspectives, these abilities might be relevant to study in children who develop a neuropsychiatric diagnosis later on or in infants who later show impaired ability to imitate. Theoretical in the sense that it will provide insight into the earliest signs of intersubjectivity – i.e. primary intersubjectivity – and how this knowledge might influence our understanding of children following atypical trajectories of development. Practical in the sense that it might lead to earlier detection of certain disabilities. In the present work, we screened the literature for empirical studies on neonatal imitation in children with an Autism spectrum disorder (ASD) or Down syndrome (DS) as well as present an observation of neonatal imitation in an infant that later was diagnosed with autism and a re-interpretation of previously published data on the phenomenon in a small group of infants with DS. Our findings suggest that the empirical observations to date are too few to draw any definite conclusions but that the existing data suggests that neonatal imitation can be observed both in children with ASD and in children with DS. Thus, neonatal imitation might not represent a useful predictor of a developmental deficit. Based on current theoretical perspectives advocating that neonatal imitation is a marker of primary intersubjectivity, we propose tentatively that an ability to engage in purposeful exchanges with another human being exists in these populations from birth.